Meet big foot - Nagler, Michelle H.; Del Sur, Duendes; Cartoon Network (Television network) (New York, NY : Scholastic Inc., 2002)
Is Big Foot hiding in the woods? It's another mystery for Scooby-Doo.
At head of title: Cartoon Network.